Trivium art history (2015)
[Dt.:] Trivium Art History ist eine kunsthistorische Internetquelle die mehr als 1000 Kunstwerke verzeichnet. Die Kunstwerke stehen teilweise zum Download zur Verfügung. Die Datenbank ermöglicht eine Suche nach Kunstwerk, Künstler, Epoche bzw. Stilrichtung und Schriften der Künstler. - [Engl.:] Trivium Art History is a new online art history resource, designed to promote exploration and discovery. Trivium hosts over 1000 high-resolution artworks, many of which are downloadable and in the public domain, and more are added daily. Their library also includes biographies of diverse artists, and features original writings by artists themselves.